2006
DOI: 10.1093/jxb/erj072
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase and programmed cell death in aleurone of ripening wheat grains

Abstract: Late maturity alpha-amylase (LMA) in wheat is a genetic defect that may result in the accumulation of unacceptable levels of high pI alpha-amylase in grain in the absence of germination or weather damage. During germination, gibberellin produced in the embryo triggers expression of alpha-Amy genes, the synthesis of alpha-amylase and, subsequently, cell death in the aleurone. LMA also involves the aleurone and whilst LMA appears to be independent of the embryo there is nevertheless some evidence that gibberelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 19 publications
3
80
0
Order By: Relevance
“…Previous studies have shown that highpI a-amylase is produced in small pockets of cells randomly distributed across the aleurone layer during a particular developmental window (Mrva et al, 2006). We failed to find any anatomical differences between aleurone cells from a constitutive +LMA genotype and a -LMA genotype, although this may have been due to a failure to section affected cells previously shown to be sparsely distributed in the aleurone (Mrva et al, 2006). However, what our anatomical studies show is that aleurone cells from +LMA and -LMA genotypes are at a similar developmental stage when LMA appears.…”
Section: Discussion Grain Development and Expression Of Lmamentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that highpI a-amylase is produced in small pockets of cells randomly distributed across the aleurone layer during a particular developmental window (Mrva et al, 2006). We failed to find any anatomical differences between aleurone cells from a constitutive +LMA genotype and a -LMA genotype, although this may have been due to a failure to section affected cells previously shown to be sparsely distributed in the aleurone (Mrva et al, 2006). However, what our anatomical studies show is that aleurone cells from +LMA and -LMA genotypes are at a similar developmental stage when LMA appears.…”
Section: Discussion Grain Development and Expression Of Lmamentioning
confidence: 99%
“…Using those cutoff criteria, only 37 probes were identified as differentially expressed at 20 and/or 23 DPA. Then, and thinking that only a very reduced proportion of aleurone cells in an LMA variety express LMA (about 2%; Mrva et al, 2006), we decided to use less stringent criteria to avoid the effects of possible gene expression dilution. So probes with 61.5-fold change between +LMA and -LMA groups and P , 0.01 were considered.…”
Section: Expression Of A-amylase Genes and Ga Response Genes In Maturmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of stress situations, this phenomenon is connected with planned dismissing of individual parts of an organism, which lose functionality (programmed cell death), such as necrosis of aleurone and seed rest, after shifting to autonomic nutrition (Mrva et al, 2006). This approach represents the first step into a new area of quantitative biology.…”
Section: Importance Of Redox Equilibriummentioning
confidence: 99%